The Benefits and Drawbacks of Kahoot: Students’ Perspective - Gartika Pandu Bhuana (Institut Agama Islam Negeri Palopo, 2022)
Technology and education are inseparable. Many schools or universities have integrated the use of technology in the classroom. The purpose is not only to bring the effectiveness of in the teaching, but also to enhance students’ motivation and participation in learning. Kahoot is one of the educational online games that is mostly used by the teacher. Unfortunately, some students think that there are problems on its usage. This study is intended to investigate the benefits and the drawbacks of Kahoot from students’ perspective. The descriptive qualitative method was considered suitable to be used. There were 50 students at one institution selected as the participants of the study. The data were collected through questionnaire and interview. Overall findings revealed that most of the students had positive attitude to the implementation of Kahoot. It offered the advantages and condition that could not be offered in conventional method. For example, it provided positive competitiveness and lively atmosphere in the class. However, some drawbacks were found. It was dealt with technical problem, such as internet connection, and the absence of discussion, and the frequency of its usage. Finally, it is suggested for the second language lecture to consider some aspects in the implementation of Kahoot.